2002
DOI: 10.1097/00075198-200210000-00016
|View full text |Cite
|
Sign up to set email alerts
|

New concepts in sepsis

Abstract: An estimated 750,000 cases of severe sepsis occur annually in the United States, and the mortality rate is about 30%. As a condition that disproportionately affects the elderly and is related to invasive and immunosuppressive healthcare, increases in the frequency of sepsis are anticipated. The complex pathophysiology of sepsis encompasses the interplay of pro- and anti-inflammatory mediators, activated circulating and resident inflammatory cells, disrupted coagulation, endothelial activation and injury, vasod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 68 publications
1
47
0
2
Order By: Relevance
“…Cardiac dysfunction during sepsis (12,22) is associated with poor outcome in both humans (2,40) and animals (7,11). We and others (19,21,23) have previously demonstrated that sepsis-or burn-associated cardiac dysfunction is primarily due to circulating myocardial depressant factors, including TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac dysfunction during sepsis (12,22) is associated with poor outcome in both humans (2,40) and animals (7,11). We and others (19,21,23) have previously demonstrated that sepsis-or burn-associated cardiac dysfunction is primarily due to circulating myocardial depressant factors, including TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recent advances in intensive care treatment and the discovery of antibiotics, sepsis remains associated with a high mortality rate (1,2). Sepsis is commonly initiated by an infection, but its pathogenesis is characterized by an overwhelming systemic inflammatory response and subsequent immune dysfunction, which can lead to lethal multiple organ failure (3).…”
mentioning
confidence: 99%
“…Despite the recent advances in intensive care treatment and the discovery of antibiotics, sepsis remains associated with a high mortality rate (1,2). Although commonly initiated by an infection, the pathogenesis of sepsis is characterized by an overwhelming systemic inflammatory response and subsequent immune dys-function, which can lead to lethal multiple organ failure (3).…”
Section: Introductionmentioning
confidence: 99%